Periodic RF transmitter geolocation using a mobile receiver - Madadi, Zahra (2016)
In this paper we propose a method to localize a periodic RF transmitter using a single mobile receiver. The receiver measures the time-of-arrival (TOA) of the periodic messages at different locations along its trajectory. By comparing the TOA of successive messages at different points along its trajectory, the receiver can eventually estimate the transmitter location. The challenge lies in separating the time offset due to receiver movement from that caused by local oscillator (LO) drift. We propose an extended Kalman filter framework that estimates the LO drift and the transmitter location simultaneously, using the TOA measurements and the receiver location as inputs. The proposed algorithm is implemented and tested on a software-defined radio testbed, and experimental results demonstrate that the proposed method is able to simultaneously locate the transmitter and estimate the LO drift with good accuracy.